83.6k views
3 votes
Describe the transformations of the graph y = (x - 3)³-2

User Olli K
by
5.0k points

1 Answer

5 votes
step - by - step

y = (x-3)^3 -2

Find the point at x=1

f(1)= ((1)-3))^3 - 2
= -8-2
y= -10

Find the point at x =2

f(2) = ((2)-3))^3 -2
= - 1-2
y = - 3

Find the point at x = 3

f(3) = ((3)-3))^3 -2
= 0-2
y= -2

Find the point at x = 4

f(4) = ((4)-3))^3 - 2
= 1-2
y= - 1

Find the point at x = 5

f(5) = ((5)-3))^3 -2
= 8-2
y = 6

Find the point at x = 6

x / y
1 -10
2 -3
3 -2
4 -1
5 6

User Sarthak Gupta
by
4.7k points